Study on the coupled coordination of water resources consumption and economic development in Heilongjiang province under different scenarios based on SD model - Meiyun Tao; Youzhu Zhao; Qiuxiang Jiang; Zilong Wang; Baohan Li (Agricultural Water Management)
Promoting the coordinated development of water resources consumption and economic growth is crucial for advancing modern society. The study constructed a novel methodological framework that utilizes the water footprint (WF) as the primary indicator. First employed a system dynamics (SD) model to construct a coupled water resources-economy composite system for Heilongjiang Province. Next, the Logarithmic Mean Divisia Index (LMDI) model and shock detection method were applied to identify and quantify the driving factors of WF. By adjusting variables, four development scenarios were designed. Finally, a coupling coordination degree model (CCDM) was employed to evaluate and select the optimal scenario with the highest system coupling coordination. This methodological framework effectively overcomes the limitations of subjective selection in control variables and scenario design. The main findings are as follows: (1) the intensity effect had the strongest inhibition of the total water footprint (WFT) from 2000 to 2021, with a contribution value of −1545.05 × 108 m³ ; structural effects had a minor impact on the WF of each sector; scale effects showed a promoting effect to the WF in all industries. (2) Simulated future trends under different development scenarios reveal that under the status quo type of development (Scenario Ⅰ), water consumption across sectors remains relatively high during 2021–2050, the WFT increase by 229.79 × 108 m³ , and with relatively slower economic growth. In contrast, under the integrated development (Scenario IV), the increase in water consumption across sectors is relatively small, the WFT increase by 145.41 × 108 m³ , alongside faster economic growth. (3) Scenario Ⅰ exhibits a low degree of coupling between the water consumption and the economic development subsystem. Scenario IV demonstrates strong coupling and a high degree of coordination between the two subsystems. Therefore, Scenario IV is identified as the optimal development scenario for the composite system. The study provides a scientific foundation for conserving regional water resources while promoting sustainable economic growth.